PENGARUH PROFITABILITAS, PERTUMBUHAN PERUSAHAAN DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN (Pada Perusahaan Food and Beverage yang Terdaftar di BEI Periode 2015-2017) - Any Tafriha Ferriyanti; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to test and analyze the effect of Profitability, Company Growth and Capital Structure on Firm Value. The population and sample are all Food and Beverage Companies that are Registered on the Stock Exchange for the 2015-2017 Period. Data analysis in this study using SPSS version 20. The sampling technique of this study using purposive sampling method and data testing techniques used in this study include normality test, classic assumption test and multiple linear regression analysis, and testing the research hypothesis. The results of this study that Profitability have a significant positive effect on firm value. Company growth has a positive and insignificant effect on firm value. Capital structure has a significant positive effect on firm value.            The results of this study indicate that: (1) profitability has a positive effect on corporate value., (2) company growth has a positive effect on corporate value and (3) capital structure has a positive effect on corporate value.Keywords: Profitability, Company Growth, Capital Structure and Corporate Value.